2018
DOI: 10.1371/journal.pone.0205085
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of social reward valuation in adults with a history of anorexia nervosa

Abstract: ObjectiveAnorexia nervosa (AN) is a disorder characterized by atypical patterns of reward valuation (e.g. positive valuation of hunger). Atypical reward processing may extend into social domains. If so, such findings would be of prognostic significance as impaired social functioning predicts worse outcome. We explore neural circuits implicated in social reward processing in individuals with a history of AN who are weight-restored relative to controls and examine the effects of illness course on the experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 78 publications
1
20
0
Order By: Relevance
“…Historical research shows that females, Caucasian females in particular, are at a much greater risk for developing an eating disorder than any other group [4,5,7,13]. Researchers have also been able to identify brain abnormalities in those diagnosed with AN while using functional magnetic resonance imaging (fMRI) and other technologies [1,2]. It has been concluded using fMRI scans that participants with a previous eating disorder diagnosis had reduced activation in the part of the brain responsible for social reward processing [2,14].…”
Section: Biologicalmentioning
confidence: 99%
See 4 more Smart Citations
“…Historical research shows that females, Caucasian females in particular, are at a much greater risk for developing an eating disorder than any other group [4,5,7,13]. Researchers have also been able to identify brain abnormalities in those diagnosed with AN while using functional magnetic resonance imaging (fMRI) and other technologies [1,2]. It has been concluded using fMRI scans that participants with a previous eating disorder diagnosis had reduced activation in the part of the brain responsible for social reward processing [2,14].…”
Section: Biologicalmentioning
confidence: 99%
“…Researchers have also been able to identify brain abnormalities in those diagnosed with AN while using functional magnetic resonance imaging (fMRI) and other technologies [1,2]. It has been concluded using fMRI scans that participants with a previous eating disorder diagnosis had reduced activation in the part of the brain responsible for social reward processing [2,14]. Additionally, Sweitzer and colleagues [2] found that the longer the person had an eating disorder, the greater decrease in brain activation.…”
Section: Biologicalmentioning
confidence: 99%
See 3 more Smart Citations